Detection of immune cell response to M. tuberculosis-specific antigens by quantitative polymerase chain reaction - Bibova, Ilona; Linhartova, Irena; Stanek, Ondrej; Rusnakova, Vendula; Kubista, Mikael; Suchanek, Miloslav; Vasakova, Martina; Sebo, Peter (Diagnostic microbiology and infectious disease, 2012)
One third of the world's population is latently infected with Mycobacterium tuberculosis (Mtb) and up to 10% of infected individuals develop active tuberculosis (TB) in their lifetime. Among the major challenges in the control of TB is the implementation of sensitive methods for detection of latent tuberculosis infection (LTBI). Currently, in vitro interferon gamma release assays, yielding single value readout, are used as an alternative to the traditional tuberculin skin test for the diagnosis of LTBI. More complex characterization of immune status of LTBI individuals, however, is desirable for indication of LTBI subjects for preventative chemotherapy. Here we describe a quantitative polymerase chain reaction (qPCR) for determination of expression levels of 14 genes, additional to interferon gamma, which was applied for comparison of the specific Mtb-antigen immune response of blood cells from healthy, latently infected, and TB individuals. With the use of principal component analysis and discriminant analysis, a pattern of mRNA levels of 6 genes was identified, allowing discrimination of healthy individuals from active TB and LTBI subjects. These results open the way to development of multimarker qPCR for the detection of LTBI.
Keywords: dospělí; Mycobacterium tuberculosis; Female; antigeny bakteriální; Adult; ženské pohlaví; Leukocytes, Mononuclear; lidé; Molecular Diagnostic Techniques; Aged, 80 and over; stanovení celkové genové exprese; Male; diagnostické techniky molekulární; latentní tuberkulóza; Aged; Antigens, Bacterial; Latent Tuberculosis; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Middle Aged; kvantitativní polymerázová řetězová reakce; Gene Expression Profiling; leukocyty mononukleární; Real-Time Polymerase Chain Reaction; Humans